Childhood Victimization by Adults and Peers and Health-Risk Behaviors in Adulthood. (2nd May 2019) - Cerezo, M. Ángeles; Pérez-García, Elena
Abstract: Victimization experienced in childhood has been linked with health-risk behaviors (HRBs) in adulthood. The purpose of this cross-sectional survey was to provide data regarding the HRBs using the ISPCAN Child Abuse Screening Tool Retrospective version (ICAST-R), Spanish version. This aimed to broaden existing knowledge by assessing both being victimized by adults and by peers in a Spanish general population of 348, aged 18–35. Age and timing of the reported victimization were also considered. Victimization: physical, psychological, sexual abuse by adults and/or peers showed a prevalence of 44.54%. Of these, 41.29% reported abuse by both. Children victimized by adults, regardless of type, were significantly associated to be psychologically abused by their peers ( p < .001). Moreover, psychological maltreatment by adults was significantly associated with two peer victimizations: Physical and psychological ( p < .001 in both). Regarding HRBs, peer victimized groups showed significantly higher levels of severity than non-victimized, with a higher proportion reporting attempted suicide ( p < .05) and psychological or psychiatric treatment ( p < .05). Participants victimized only by adults reported higher number of HRBs ( p < .01), their victimization was associated to more severe abuse of drugs/alcohol ( p ≤ .05), and suicide attempts ( p < .05). Those victimized by adults and peers received treatment in higher proportion than non-victims ( p < .001). Participants reporting victimization since before 5 years to age of 17, compared with non-victimized, showed more substance abuse ( p < .05), attempted suicide ( p < .01) and receipt of treatment ( p < .05). These findings highlight the relevance of ICAST-R in studying HRBs.